El impacto de la morosidad en las cooperativas de ahorro y crédito del Ecuador en los periodos 2019-2020. - Pineda Ríos, Yulexi Matilde; Robles Medina, Magaly Nataly (My University, 2021)
Introduction. The financial relationship of the total delinquency of the portfolio of 20 Savings and Credit Cooperatives of the financial sector of Ecuador and the current situation that exists after the health emergency, is of great economic relevance. Aim. Measure the level of delinquency for the years 2019-2020, by collecting qualitative data, to determine the degree of economic impact due to the pandemic. Materials and methods: this research has a quantitative explanatory approach, where the financial information obtained from different sources was compiled, including the Superintendency of Popular and Solidarity Economy, to carry out an analysis of the current economic situation, through formulas are intended to assess the incidence of the pandemic on customer delinquency. Results. During the period of 2019 and 2020 there were major changes that affected the delinquency rates, one of the possible causes is Covid-19. Conclution. Default increased due to the fact that the debtor did not have sufficient income to pay off the debts that they maintained in the Savings and Credit Cooperatives.
Introducción. La relación financiera de la morosidad total de la cartera de 20 Cooperativas de Ahorro y Crédito del sector financiero del Ecuador y la situación actual que se vive tras la emergencia sanitaria, es de gran relevancia económica. Objetivo. Medir el nivel de morosidad de los años 2019-2020, mediante la recopilación de datos cualitativos, para la determinación del grado de afectación económica debido a la pandemia. Materiales y métodos: la presente investigación tiene un enfoque cuantitativo de tipo explicativo, en donde se recopiló la información financiera obtenida de diferentes fuentes, entre estas la Superintendencia de Economía Popular y Solidaria, para realizar un análisis de la situación económica actual, a través de fórmulas se pretende evaluar la incidencia de la pandemia sobre la morosidad de los clientes. Resultados. Durante el periodo del 2019 y 2020 se presentaron grandes cambios que afectaron los índices de morosidad, uno de las posibles causas es el Covid-19. Conclusión. La morosidad aumentó debido a que el deudor no disponía de ingresos suficientes para saldar las deudas que mantenían en las Cooperativas de Ahorro y Crédito.
Keywords: COOPERATIVAS DE AHORRO; MOROSIDAD; ECUADOR